MODERN APPROACHES TO LESSON PLANNING: MODERN APPROACHES TO LESSON PLANNING - Omonova, Kamola (Журнал иностранных языков и лингвистики, 2025)
Lesson planning is a crucial aspect of effective teaching and learning. Traditional methods of lesson planning have evolved significantly with the advancement of educational theories, technology, and student-centered approaches. This paper explores modern approaches to lesson planning, including student-centered learning, technology integration, differentiated instruction, competency-based education, gamification, and interdisciplinary strategies. By implementing these approaches, educators can enhance student engagement, improve learning outcomes, and prepare students for real-world challenges. The paper also reviews relevant literature supporting these methods and provides practical recommendations for educators.